PENGARUH KOMPETENSI APARATUR DESA, SISTEM PENGENDALIAN INTERNAL, INTEGRITAS DAN AKUNTABILITAS TERHADAP PENCEGAHAN KECURANGAN (FRAUD) DALAM PENGELOLAAN KEUANGAN DESA. - Ni Kadek Rai Eldayanti; Sang Ayu Putu Arie Indraswarawati; Ni Wayan Yuniasih (Hita Akuntansi dan Keuangan, 2020)
Fraudl preventionl in managingl villagel finances is importantl in implementingl villagel governance. Thisl study aims to determine thel effect ofl villagel apparatus competence, internall control systems, integrity, andl accountability on thel preventionl ofl fraudl in thel management ofl villagel finance in villages in thel shrinkingl sub-districts. Thel populationl in thisl study were all villagel officials in villages in thel sub-district ofl Shrink sub-district, respondentsl were used as many as 72 people consistingl ofl thel Villagel Head, Villagel Secretary, Head ofl Government, Head ofl Public Welfare, Head ofl Service, Head ofl Finance, Head ofl General andl Planning. Thel method ofl determiningl thel sample usingl a purposive samplingl technique. From thel results ofl thisl study thel competence ofl villagel officials, internall control systems, andl integrity did not significantly influence fraudl prevention. While accountability has a negative andl significantl effect on preventingl fraudl (fraudl) in thel management ofl villagel finances in villages in thel shrinkingl sub-district.